EVALUATION OF BLOOD PRESSURE, CHOLESTEROL, GLUCOSE, AND URIC ACID LEVELS IN PATIENTS AT THE OLAK KEMANG HEALTH CENTRE IN JAMBI CITY - Attiya Istarini; Lipinwati; Hasna Dewi; Wulandari, Putri Sari; Samsirun Halim; Amatullah, Afifah; Hafizah; Denok Tri Hardiningsih (Universitas Jambi, 2025)
ABSTRACT Hypertension is a chronic elevation of systemic arterial pressure beyond a level that may damage the endothelium. Individuals with hypertension typically demonstrate increased levels of blood glucose, cholesterol, and uric acid. Hyperlipidemia, age, and hypertension exhibit a complicated interplay that profoundly influences cardiovascular risk. Inadequate management of blood pressure and insufficient public awareness regarding the early detection of metabolic syndrome continue to significantly worsen the global prevalence of cardiovascular disease.This community service initiative assessed blood pressure and blood chemistry to identify early risk factors for cardiovascular disease. Olak Kemang Health Centre, affiliated with Jambi University's Faculty of Medicine and Health Sciences, conducts community service projects. Patients of the Regular Olak Kemang Health Center engaged in this research. Following an 8-hour fasting period, all individuals underwent assessments of their blood pressure, cholesterol levels, glucose, and uric acid concentrations. This study evaluated the blood pressure and clinical chemistry of 44 subjects. Seven patients (15.9%) exhibited pre-hypertension, twelve (27.3%) presented with stage 1 hypertension, and eleven (25%) were diagnosed with stage 2 hypertension. The majority of individuals with hypertension were aged 46 to 55 years. In the community service, 4 participants exhibited elevated uric acid levels, 9 had elevated glucose levels, and 7 had elevated cholesterol levels. Eight patients with stage 1 hypertension exhibited higher blood chemistry levels. Considering that glucose, cholesterol, and uric acid are associated with cardiovascular disease risk, it is advisable for patients with hypertension to have their levels regularly monitored. Their connection highlights the need for integrated management strategies to improve patient care and prevent complications. Keywords: Elderly, Hypertension, Hyperlipidemia, Hyperglicemia, Hyperuricemia. ABSTRAK Hipertensi adalah peningkatan kronis tekanan arteri sistemik di atas level yang dapat merusak endotelium pembuluh darah. Individu dengan hipertensi biasanya menunjukkan peningkatan kadar glukosa darah, kolesterol, dan asam urat. Hiperlipidemia, usia, dan hipertensi menunjukkan interaksi yang meningkatkan resiko kejadian penyakit kardiovaskular. Manajemen tekanan darah yang tidak memadai dan kurangnya kesadaran publik mengenai deteksi dini sindrom metabolik terus memperburuk prevalensi penyakit kardiovaskular global secara signifikan. Kegiatan pengabdian masyarakat ini bertujuan untuk pemeriksaan tekanan darah dan kimia darah untuk mengidentifikasi lebih awal faktor risiko penyakit kardiovaskular. Kegiatan ini diinisiasi oleh Fakultas kedokteran dan Ilmu Kesehatan Universitas Jambi bekerja sama dan dilaksanakan di Puskesmas Olak Kemang Kota Jambi. Pasien Puskesmas Reguler Olak Kemang terlibat dalam kegiatan ini. Setelah puasa selama 8 jam, semua individu menjalani penilaian tekanan darah, kadar kolesterol, glukosa, dan konsentrasi asam urat. Studi ini mengevaluasi tekanan darah dan kimia klinis dari 44 peserta. Tujuh orang (15,9%) menunjukkan pra-hipertensi, dua belas orang (27,3%) menunjukkan hipertensi stadium 1, dan sebelas orang (25%) didiagnosis hipertensi stadium 2. Mayoritas individu dengan hipertensi berusia 46 hingga 55 tahun. Dalam pengabdian masyarakat, empat orang menunjukkan peningkatan kadar asam urat, sembilan orang memiliki peningkatan kadar glukosa, dan tujuh orang memiliki peningkatan kadar kolesterol. Delapan pasien dengan hipertensi stadium 1 menunjukkan kadar kimia darah yang lebih tinggi. Mengingat bahwa glukosa, kolesterol, dan asam urat berhubungan dengan risiko penyakit kardiovaskular, disarankan bagi pasien hipertensi untuk memantau kadar kimia darah secara teratur. Hubungan antara hipertensi dan sindrom metabolik menunjukkan perlunya strategi manajemen terpadu untuk meningkatkan perawatan pasien dengan hipertensi dan mencegah komplikasi. Kata kunci: Lansia, Hipertensi, Hiperlipidemia, Hiperglikemia, Hiperurisemia